The Influence of Advertising and Influencer in Shaping Mineral Water Brand Purchase Intention in Jakarta, Indonesia - Davin Hillaro Siahaan; Indra Batara Siahaan (Universitas Pelita Harapan, 2026)
Mineral water is a promising business industry in Jakarta, since Jakarta is a metropolitan city in Indonesia and has big market size. Many mineral water brands have implemented several ways of advertising. Three of those through social media, traditional, and influencer marketing. However, there is unclarity framework to identify in depth the correlations between advertising implementation on consumers’ purchase intention. This research aimed to obtain which type has the most influential effect. A quantitative study has been conducted, maximizing several tests from SPSS for the data gathered through online questionnaire from 222 respondents from multiple demographic variables. The results uncovered that all three variables identified had positive correlations on purchase intention, which social media advertising showed the strongest relationship. This result answers previous research mentioned there is no clear framework and clarity in identifying the more attractive advertising influences on higher purchase intention, and which type of advertising dominantly influences. Therefore, the role of integrated marketing communications is advisable to be implemented. This research can be utilized as a guide for marketing managers in creating marketing strategies, as a reference for the next researcher, and readers to enrich knowledge especially in aspect of advertising strategies.